Description of the first species of Cymodusa Holmgren from Brazil (Hymenoptera, Ichneumonidae, Campopleginae) - Onody, Helena C.; Penteado-Dias, Angélica Maria (Zootaxa, 2019)
Cymodusa ypy sp. nov., the first species of the genus to be formally described from Brazil, is described and illustrated. This record extends significantly the known distribution of the genus in the Neotropical region.